Activation of rhodium selenides for boosted hydrogen evolution reaction via heterostructure construction. (May 2021) - Pan, Shuyuan; Ma, Shuangxiu; Chang, Chaofeng; Long, Xue; Qu, Konggang; Yang, Zehui
Abstract: Constructing a high-performance hydrogen evolution reaction (HER) electrocatalyst is significantly desirable to realize electrochemical splitting of water to massively produce hydrogen. In this work, we have activated rhodium selenides by incorporation of metallic Rh to form Rh–Rh3 Se4 heterostructure at atomic level to regulate the electronic configuration of Rh3 Se4 . Due to the presence of metallic Rh, the HER activity of Rh–Rh3 Se4 /C is boosted requiring an ultralow overpotentials of 32 mV and 29 mV to attain 10 mA cm −2 in acidic and alkaline electrolyte with 14.3 μgRh cm −2, respectively, corresponding to 11- and 6.5-fold better mass activity than commercial Pt/C at overpotential of 50 mV. The exceptional HER performance is attributed to the metallic Rh efficiently weakening the strong binding strength between Rh3 Se4 and hydrogen ions associated with constructing electronic path to decrease the charge transfer resistance due to the electronic enrichment at Fermi level. Besides, owing to the strong electronic interaction between metallic Rh and Rh3 Se4, a superior HER stability is also achieved. Graphical abstract: Image 1 Highlights: Rh–Rh3 Se4 /C heterostructure electrocatalyst is formed for efficient HER catalysis. Rh–Rh3 Se4 /C performs 11-fold better mass activity than commercial Pt/C in acidic medium. 6.5 fold better HER activity is recorded for Rh–Rh3 Se4 /C than Pt/C in alkaline medium.